An observational study on lifestyle and environmental risk factors in patients with acute appendicitis. Issue 4 (April 2023) - Peeters, Toon; Houben, Bert; Cools, Peter; Thys, Yati; D'Onofrio, Valentino; Martens, Sandrina; Jaeger, Martin; Doppenberg-Oosting, Marije; Netea, Mihai G.; Gyssens, Inge C.
Abstract: Purpose: Acute appendicitis is a common abdominal emergency worldwide. This study aimed at characterizing environmental risk factors influencing the development and severity of acute appendicitis. Methods: Patients from a Belgian acute appendicitis cohort (n = 374) and healthy controls from the 500 functional genomics (500FG) cohort (n = 513) were compared. Individuals with a history of appendectomy (n = 1067) and without a history of appendectomy (n = 8656) were available from the Nijmegen Biomedical Study (NBS). Questionnaires on demographics, lifestyle and environment were available. Binary logistic regression was used for prediction models. Results: Fifteen risk factors for developing acute appendicitis were identified. Binary logistic regression showed that 7 were independent risk factors: family history of acute appendicitis, having grown up in a rural environment, having a lower education, probiotic use as well as antibiotic use increased the risk of developing appendicitis. Fruit and fiber-rich vegetable consumption decreased the risk. Findings on vegetable consumption, smoking and level of education were replicated in the NBS population. Independent risk factors for complicated appendicitis were being male, higher age, and a delay to diagnosis of more than 48 h. Conclusions: Environmental exposures influence the risk of developing appendicitis. Further research into these factors is needed.